Housing Cooperatives: Exploring Sustainable, Affordable, and Inclusive Living - Nofitasari, Diah; Subagyo, Ahmad; Sumaryana, Fitriana Dewi; Ikhsan, Sugiyanto (EKOMA : Jurnal Ekonomi, Manajemen, Akuntansi, 2026)
This study addresses the persistent global housing crisis, marked by rapid urbanization, rising land and construction costs, and increasing income inequality. The research aims to critically analyze housing cooperatives as a sustainable and inclusive solution to these challenges, focusing on their capacity to provide adequate and affordable housing where market-driven models have fallen short.A qualitative approach is adopted, combining an extensive literature review with comparative case studies from Indonesia, India, Jordan, Australia, Saudi Arabia, and Europe. The analysis covers the historical development, legal and policy frameworks, financing models, governance structures, and social and environmental impacts of housing cooperatives. The findings reveal that housing cooperatives significantly enhance affordability, promote social inclusion, and strengthen community resilience, especially when supported by enabling legal frameworks, innovative financing, and strong participatory governance. However, challenges such as regulatory complexity, limited access to long-term funding, and low public awareness persist. To maximize the potential of housing cooperatives, the study recommends strengthening legal recognition, fostering financial innovation, building institutional capacity, and encouraging multi-stakeholder collaboration. These measures are essential for advancing equitable and sustainable urban development.